Spectroscopic and Electrochemical Studies of the Interaction of Some Gold(III) Complexes with Biologically Relevant Thiones. Issue 3 (22nd January 2018) - A. Sulaiman, Adam A.; Omer, Khalid H.; Kawde, Abdel‐Nasser; M. Wazeer, M. I.; Altaf, Muhammad; Musa, Musa M.; Ahmad, Saeed; Isab, Anvarhusein A.
ABSTRACT: The interaction of gold(III) complexes, [Au( cis ‐DACH)Cl2 ]Cl and [Au( cis ‐DACH)2 ]Cl3 complexes (DACH = cis ‐1, 2‐diaminocyclohexane), with 13 C, 15 N‐enriched thiourea (Tu) and 1, 3‐diazinane‐2‐thione ligands was investigated. The progress of these reactions was monitored by NMR ( 1 H, 13 C, and 15 N) and UV–vis spectroscopy as well as square wave stripping voltammetry. The kinetic studies of the substitution reactions between the above‐mentioned complexes with thiones in aqueous solutions containing 30 mM KCl, which is used to suppress the hydrolysis of the chloride complexes, were conducted. These reactions were followed under pseudo–first‐order conditions as functions of ligand concentration, pH, and temperature. The activation parameters (Δ H #, Δ S # ) were calculated from Eyring plots, and the negative values of Δ S ≠ lend support for an associative mechanism. The kinetic data also indicated a relatively higher reactivity of [Au( cis ‐DACH)Cl2 ]Cl than that of [Au( cis ‐DACH)2 ]Cl3 toward the thiones.